2014
DOI: 10.1016/j.ejrad.2014.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Supply and demand for radiographers in Lithuania: A prognosis for 2012–2030

Abstract: Considering the changes in education of radiographers, the socio-demographic characteristics of the staff, and the increasing need for radiographers' services, the supply of radiographers during the next two decades will be insufficient. To meet the forecasted demand for radiographers in the perspective scenario, the number of students choosing this specialty from 2013 on should increase by up to 30%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 7 publications
0
10
0
2
Order By: Relevance
“…In addition, this study revealed a gap forming between the need for human resources in relationship to the need for services, equipment, and examinations. Findings from the study predicted that there will be a shortfall of radiographers during the 18 years analyzed, with a significant expected shortfall to be reached by 2030 [17].…”
Section: Resourcesmentioning
confidence: 97%
See 2 more Smart Citations
“…In addition, this study revealed a gap forming between the need for human resources in relationship to the need for services, equipment, and examinations. Findings from the study predicted that there will be a shortfall of radiographers during the 18 years analyzed, with a significant expected shortfall to be reached by 2030 [17].…”
Section: Resourcesmentioning
confidence: 97%
“…This will allow for expansion in this area of study at a later date. For example, a research study that focused on the supply and demand of radiographers in Lithuania was conducted in 2012 [17]. The aim of this study was to analyze the need and demand for radiographers and to provide a prognosis for the time period of 2012-2030 [17].…”
Section: Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Metodika. Į radiologijos technologo studijas priimamų studentų skaičiaus prognozė yra dalis platesnio tyrimo "Radiologijos technologų pasiūlos ir poreikio prognozė Lietuvoje 2012 -2030 m.", kuriame buvo prognozuota specialistų pasiūla ir poreikis pagal du scenarijus: vidutinį ir perspektyvinį [20]. Šiame tyrime, vertinant ir lyginat tarpusavyje, labiausiai tikėtinas radiologijos technologų pasiūlos ir poreikio prognozes perspektyvinių scenarijų atvejais buvo prognozuotas reikiamas stojančių į studijas skaičius iki 2030 m., siekiant patenkinti specialistų poreikį darbo rinkoje.…”
Section: Santraukaunclassified
“…Šis radiologijos technologų programose studijuojančių studentų poreikio tyrimas atliktas remiantis daug platesne tyrimo metodika, kuri jau buvo taikyta atliekant tyrimą "Radiologijos technologų pasiūlos ir poreikio prognozė Lietuvoje 2012-2030 m." [20]. Priimamų studentų skaičius kasmet į "Radiologijos" studijų programas, kurios vykdomos nuo 2013 metų Kauno kolegijoje ir Klaipėdos universitete, prognozuotas remiantis bei tarpusavyje lyginant labiausiai tikėtinus -perspektyvinius radiologijos technologų pasiūlos ir poreikio prognozavimo scenarijus [20].…”
Section: Medžiaga Ir Metodikaunclassified